Distribution of antimicrobial resistance genes of methicillin-resistant Staphylococcus aureus isolated from animals and humans in Yogyakarta Indonesia - Mulya Fitranda; Siti Isrina Oktavia Salasia; Osman Sianipar; Usi Sukorini; Fatkhanuddin Aziz; Madarina Wasissa; Fajar Budi Lestari; Riat El Khair; Andaru Dahesihdewi (International Journal of One Health, 2024)
Background and Aim: Methicillin-resistant Staphylococcus aureus (MRSA) has been known as a highly pathogenic bacteria in animals and humans, which is still becoming a global health issue. The prevalence of MRSA infection continues to increase worldwide and has become a global concern as a dangerous zoonotic disease. The World Health Organization estimates that by 2050 MRSA will be the leading cause of death. This study aimed to estimate the prevalence of MRSA in S. aureus isolates of veterinary and human origin in Yogyakarta, Indonesia.